Imipenem and Meropenem: Comparison of In Vitro Activity, Pharmacokinetics, Clinical Trials and Adverse Effects - George G Zhanel; Andrew E Simor; Lavern Vercaigne; Lionell Mandell; the Canadian Carbapenem Discussion Group (Canadian Journal of Infectious Diseases)
OBJECTIVE: To compare and contrast imipenem and meropenem in terms of in vitro activity, pharmacokinetics, clinical efficacy and adverse effects.